Structure and classification of e-business models - V.О.; S.V. (Економіка, управління та адміністрування, 2022)
The article argues the need to use business models to ensure the sustainable and efficient functioning of modern enterprises. The business model is defined as a simplified representation of the mechanism for carrying out activities. Since the digitalization of business processes occurs through the active introduction of information and communication technologies, Big Data, cloud technologies, usually with the use of artificial intelligence, digitalization of business processes is taking place, there is a need to optimize, transform existing and develop new business models. In this regard, companies with digital business models are entering the market. The authors propose an approach to defining an e-business model as a conceptual and architectural implementation of an enterprise’s business strategy and the basis for implementing business processes. The exclusive interest in the study of e-business models is associated with the benefits that they provide to companies, namely: help to identify and better understand the relevant elements in a particular area and the relationship between them; improve communication between managers and their ability to share their understanding of e-business with stakeholders; help to model e-business and study it. Based on the results of the study, the structure of the e-business model is given. It includes values for end users (customers), infrastructure and network of partners, customer relationships. The necessary finances take place in each of the named parts of the structure. There are traditional kinds of business models and business models in e-business. In general, the traditional business model is primarily called the holistic structure of reflecting the mechanism of doing business, actively used to test business proposals on the market. Therefore, the classification of these types of business models takes into account the types of customers in the market and the way something is converted into legal tender (i.e., monetized). A wide range of business models in e-business has also been formed. Among them, the leading place is occupied by the affiliate marketing model, the business model using blockchain technologies, and the freemium. This classification allows us to understand the overall impact of digitalization on business processes and the use of the concept of business modeling for the purpose of sustainable development and improving the efficiency of a modern enterprise.